Shear bond behaviour of composite slab made of cold foamed steel deck and asphaltic concrete [electronic resource] - 195156 Ann, See Peng; Fakulti Kejuruteraan Awam (2007)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Struktur dan Bahan)) - Universiti Teknologi Malaysia, 2007